Hypoglycemia at the time of Covid-19 pandemic (2020)
Background: Hypoglycemia is the limiting factor in the glycemic management of diabetes, which need to be addressed critically to avoid complications. Lockdown because of new coronavirus strain (COVID-19) pandemic has further complicated the issue of hypoglycemia due to limitations in access to food, outpatient clinics, pathological services and medicines. Aim: To assess the factors associated with the risk of hypoglycemia during AprileMay 2020 lockdown in people with type 2 diabetes mellitus. Methodology: We analyzed the data retrospectively from 146 patients of type 2 diabetes mellitus (T2DM) reporting to the emergency department (ED) during lockdown period with symptoms suggestive of hypoglycemia. Results: The majority of patients were male (90/146) with a mean age of 59.88 ± 10.09 years and a mean random blood glucose level of 57.67 ± 9.00 mg/dL. Two-third of patients (70.83%) had level 1 hypoglycemia, while level 2 hypoglycemia was reported in 29.16% of patients. A combination of Metformin and Sulfonylureas (SU) was most commonly associated with the risk of hypoglycemia (65.75%) followed by insulin (33.56%). Subjects who received insulin reported a lower blood glucose value (50.75 ± 8.20 mg/dL) as compared to those receiving a combination of metformin and SU (60.95 ± 7.10 mg/dl). 330.56% of patients who had received prophylaxis hydroxychloroquine (HCQ) 400 mg twice a day along with the routine anti-hyperglycemic agents without their dose adjustment reported hypoglycemia. Patients with hypertension, micro-vascular, macro-vascular complications, and coexistent with each other had a higher propensity to the risk of hypoglycemia (46.58%, 33.56%, 23.29%, and 32.88%) respectively. Conclusion: The COVID-19 lockdown has shown to influence the risk of hypoglycemia in patients with T2DM, especially those receiving SU, insulin, HCQ especially in patients with associated co-morbidities. Patient education, support, and telemedicine plays a pivotal role to prevent hypoglycemia